PENGARUH PENAMBAHAN MINERAL MIKRO ORGANIK DAN SILASE DAUN SINGKONG TERHADAP TDN ( Total Digestible Nutrient) DAN ENERGI TERCERNA RANSUM BERBASIS LIMBAH KELAPA SAWIT PADA SAPI POTONG CALON INDUKAN - Agus Irawan, Liman, Agung Kusuma Wijaya, Dan Muhtarudin (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
This study aims to determine the effect of adding microorganic mineral and Silage of cassava leaves to TDN (Total Digestible Nutrient) and digestible energy based on palm oil waste on heifer. The study was conducted in March-May 2018 at the Animal Nutrition and Feed Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The material of this study using 9 Ongole cattle grade and grouping based on body weight. This study used a randomized block design with 3 treatments and 3 replications. The research treatment consisted of R0 (ration control), R1 (R0 + organic minerals (Zn 40 ppm, Cu 10 ppm, Cr 0.30 ppm, and Se 0.10 ppm) and R3 (R1 + 15% cassava leaves (branched amino acid source / brand chain amino acid) The results showed that: The provision of rations based on oil palm waste significantly affected TDN (Total Digestible Nutrient) and did not significantly affect digestible energy in the Ongole Breeders cow, fermented waste palm oil rations (R2) produced the highest and optimum TDN average is 72.11%, the ration based on fermented palm oil (R2) produces the highest and optimum digestible energy average of 15381.57Kcal / head / day. Keyword: Digestible energy, Palm oil waste, Organic micro minerals, Silage of cassava leaves, Total digestible nutrient